2022
DOI: 10.1088/1748-0221/17/09/p09026
|View full text |Cite
|
Sign up to set email alerts
|

Performance in beam tests of irradiated Low Gain Avalanche Detectors for the ATLAS High Granularity Timing Detector

Abstract: The High Granularity Timing Detector (HGTD) will be installed in the ATLAS detector to mitigate pile-up effects during the High Luminosity (HL) upgrade of the Large Hadron Collider (LHC) at CERN. The design of the HGTD is based on the use of Low Gain Avalanche Detectors (LGADs), with an active thickness of 50 μm, that allow to measure with high-precision the time of arrival of particles. The HGTD will improve the particle-vertex assignment by measuring the track time with a resolution ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…At DESY, a silicon photomultiplier (SiPM) combined with a quartz bar provided a time reference that was acquired by the DAQ together with two DUTs. The measured time resolution from this device was found to be 62.6±0.6 ps for an operating voltage of 27 V. This time resolution was degraded compared to the previous measurements [11] due to ageing and irradiation effects.…”
Section: Set-up At Desymentioning
confidence: 55%
See 3 more Smart Citations
“…At DESY, a silicon photomultiplier (SiPM) combined with a quartz bar provided a time reference that was acquired by the DAQ together with two DUTs. The measured time resolution from this device was found to be 62.6±0.6 ps for an operating voltage of 27 V. This time resolution was degraded compared to the previous measurements [11] due to ageing and irradiation effects.…”
Section: Set-up At Desymentioning
confidence: 55%
“…In beam tests [11] as well as in laboratory measurements [12], it was observed that the addition of carbon in the gain layer helps reducing the operating voltage needed to collect the same charge by a reduction of the acceptor removal rate after irradiation, hence improving the radiation hardness [13] of the sensors. This is extremely important at higher fluences where standard LGADs need a rather high voltage to maintain their performance (gain, time resolution) after irradiations.…”
Section: Jinst 18 P05005mentioning
confidence: 99%
See 2 more Smart Citations
“…annealing time would have any impact on the occurrence of mortality. The performance of these type-3.1 and 3.2 sensors were tested at HGTD beam tests in 2018 and 2019 [17]. HPK-P1 sensors of type-1.1 and 1.2 were chosen to give a clearer picture if mortality was impacted by the sensor active material thickness, as they are thinner than the more recently produced LGADs at 35 µm versus the more typical ∼50 µm.…”
Section: Jinst 18 P07030mentioning
confidence: 99%